Organic photovoltaic devices based on blends of regioregular poly(3-hexylthiophene) and poly(9,9-dioctylfluorene-co-benzothiadiazole) - Choulis, Stelios A.; Kim, Youngkyoo; Cook, Steffan (My University, 2004)
We have fabricated organic photovoltaic devices with blends of regioregular poly(3-hexylthiophene) (P3HT) and poly(9,9-dioctylfluorene-co-benzothiadiazole) (F8BT) as an electron donor and an electron acceptor, respectively. Several fabrication parameters such as blend composition, film thickness, solvent, and presence of LiF layer were varied in order to find the maximum device performance. The highest external quantum and power conversion efficiencies were achieved for the blend film with 60 wt % P3HT using p-xylene as a solvent. Insertion of a LiF layer further improved the power conversion efficiency from 0.02% to 0.13% under AM1.5 condition (1 Sun). To understand the relatively poor efficiency even in the optimized device, this polymer blend system was analyzed in relation to the following factors: charge separation efficiency, as measured by photoluminescence quantum efficiency; charge carrier mobility, measured by time-of-flight; and charge recombination dynamics, measured by transient absorption spectroscopy. The results showed that the electron mobility of F8BT is responsible mainly for the low efficiency in the presence of minor contribution of the charge separation efficiency
Keywords: Photoelectric cells; Absorption spectroscopy; Photoluminescence; Film; Quantum chemistry